Returning to sport after pregnancy: A qualitative study of elite female athletes in the UK - Caro, C. V.; O'Leary, N.; Trow, S.; Bell, Z.; Payne, E.; Silverio, S. A.; Lavelle, F.; Flynn, A. C. (Journal of Science and Medicine in Sport, 2026)
Objectives Elite athletes are more commonly returning to sport after pregnancy. Whilst research and policies to support athletes after pregnancy are increasing, understanding the lived experiences of United Kingdom (UK) elite athletes as they return to sport remains limited. This study aimed to examine the experiences and perspectives of UK elite athletes from a range of sports on the postpartum period and the return to sport.